Utility of high‐risk HPV RNA chromogenic in situ hybridization in cytology smears and liquid‐based preparations from metastatic head and neck squamous cell carcinoma. Issue 3 (9th November 2022) - Velez Torres, Jaylou M.; Alkathery, Turky; Tjendra, Youley; Zuo, Yiqin; Kerr, Darcy A.; Gomez‐Fernandez, Carmen
Abstract: Background: High‐risk human papillomavirus (HR‐HPV) status is critical for the diagnosis, prognosis, and treatment of patients with oropharyngeal squamous cell carcinoma (OPSCC). Patients often present with enlarged cervical nodes, and fine‐needle aspiration cytology (FNAC) is frequently the initial diagnostic procedure. Although p16 is the most widely used surrogate marker, problems with interpretation can limit its utility in FNAC. HR‐HPV RNA in situ hybridization (ISH) has emerged as a specific way to assess HPV status on cell block preparations of cervical nodes. The authors evaluated the utility of HR‐HPV ISH in conventional smears and liquid‐based cytology (LBC) preparations of metastatic head and neck squamous cell carcinoma (SCC). Methods: Thirty‐one aspirates of proven, HPV‐related SCC (confirmed by p16 and/or HR‐HPV ISH in corresponding surgical specimens) were selected. Ten aspirates of HPV‐negative SCC were also retrieved. HR‐HPV ISH was performed on 27 smears and 14 LBC preparations. All results were scored as positive, equivocal, or negative. Results: Eighty‐four percent of metastatic, HPV‐related SCCs were positive for HR‐HPV RNA ISH, with high number of signals ( n = 19) and low number of signals ( n = 7), whereas five HPV‐related SCCs were equivocal. All metastatic, HPV‐negative SCCs were negative for HR‐HPV ISH. Conclusions: HR‐HPV ISH can be reliably performed on smears or LBC preparations, particularly when cell blocks are unavailable or paucicellular. Results were easy to interpret when high numbers of signals were present but were challenging in aspirates with low or rare number of signals. The current study suggests that HR‐HPV ISH could be used as the initial testing modality for determining HPV status in FNAC specimens of metastatic SCC. Abstract : High‐risk human papillomavirus RNA in situ hybridization can be reliably performed on conventional smears or liquid‐based cytology. It could also be used as the initial testing modality for determining human papillomavirus status in patients with metastatic head and neck squamous cell carcinoma.